Synthesis of Surfactant Tert-Butyl Glycosides from Glucose and Tert-Butanol - Harsa Pawignya; Tutuk Djoko Kusworo; Bambang Pramudono (Reaktor, 2018)
In Indonesia, a lot of discarded agricultural waste still contains cellulose (35-50%), the waste can still be hydrolyzed to glucose and then used as raw material in the manufacture of surfactants. Glucose can be reacted with tert-butanol using a para-toluene sulfonic acid catalyst to form tert-butyl glycoside surfactant. The purpose of this study was to study the process conditions influence the variable mole ratio, temperature, and catalyst percent on the yield of tert-butyl glycosides. The results showed that at mole ratio 1:5; temperature 70oC; and the percentage of catalyst 2.5 %, the yield obtained was 98.58 % with tert-butyl glycosides content of 61.2 %. Furthermore, the molecular structure of the surfactant was analyzed using FTIR while surface tension to determine the hydrophilic-lipophilic balance (HLB) value and obtained an HLB value of 4.61 Therefore, tert-butyl glycoside surfactant can be used as an emulsifier in the water-in-oil emulsion system.Keywords: glucose; surfactant; tert-butanol; tert-butyl glycosides